Impact of cartoon images on kids and their parents buying behavior with reference to cheetos and kinder joy (muscat, oman) - Arshiya Sultana; Assad Al Namani; Iman Al Balushi; Latifa Al Balushi; Loay AlHajri; Noor Al Zadjali (Journal of Management and Science, 2022)
This study was implemented to examine the impact of cartoon images on kids and their parents buying behavior of food products with a reference to Cheetos and kinder joy. The objectives of this research are: 1) identifying the effects of cartoon images on kids and their parents buying behavior. 2) Focusing on factors, which motivate their parents to make buying decision. 3) Finding out the creative strategies to enhance product development. To carry on the research, literature from previous researches on a similar topic was reviewed.The questionnaire for this research were designed using a mixed-method (50 questionnaire and 5 interviews). The sample that we will use to distribute the surveys and conduct interview is convenience,non-probability sampling method. The research covers 50 participants who have kids from 4-10 years or they are in position of parents of their brothers, sisters, nieces or nephews. Also, the interviews are conducted in the malls (LULU Hyper Market Carrefour). The data collection is done through online qualitative research (online questionnaire), while the interview questionsare semi-structured and are analyzed by generating keywords for each question.The analysis of the questionnaire is done using the SPSS analysis software and MS. Excel as the long questions was entered in the software by categorizing them in themes.The results of the study shown that both Kinder joy and Cheetos are well known. In fact, most of the children are influenced consumer behavior, kids, parents baying behavior, packaging, cartoon images, Cheetos, Cheetah Chester, kinder joy.by the cartoon images of those brands.